DNA Barcoding COMO FERRAMENTA DE DESCRIMINAÇÃO DE COMPLEXOS CRÍPTICOS EM PEIXES NEOTROPICAIS: uma história do gênero Moenkhausia C. H. EIGENMANN, 1903 no nordeste Paraense. - MONTEIRO, Altemir Soares (2024)
The mega-diversity of the Neotropical fish species is the richest in the world. The diversity of freshwater fish in South America is centered in the Amazon, the fish make up the oldest and largest group among the existing vertebrates, represented by extremely diverse forms and adapted to the most different environmental conditions. The genus Moenkhausia, is currently one of the genera with the highest diversity of species in the Characidae family. The genus comprises species with a wide variety of body shapes and coloring patterns, with such a diversity, several species of the genus Moenkhausia have been described in recent years, in this way, it is primordial to accelerate and simplify the process that involves the identification of species within the genre. In this sense, due to certain limitations in classifying the living beings only by morphological traits, the method of classifications based on DNA analysis has been gaining prominence in the last years, therefore, it is mainly in this context of identification of the diversity that the genetic markers are being applied and molecular changes in neotropical fish species. Thus, the DNA Barcoding analysis method is an innovative system that has shown to be significant to identify and classify species quickly and accurately. Thus, this work intends to genetically discriminate the possible strains of fish of the genus Moenkhausia that occur in different regions of the state of Pará through the DNA barcoding tool. Between the years 2008 and 2011, Moenkhausia samples were collected in different regions of the state of Pará, in a total of 54 individuals. The results obtained here shows at least 17 filogenetic clades well supported and also, indicates that the species M. sanctafilomenea e M oligolepsi aren’t monophyletic linaeges. The results generated in the present study point to the effectiveness of DNA barcoding in discriminating distinct molecular strains within neotropical fish, reinforcing the usefulness of the DNA barcoding tool in discriminating distinct evolutionary strains for neotropical freshwater fish.